Young socialists in the modern world. 6th International Congress of I[nternational] U[nion of] S[ocialist] Y[outh] Vienna, October 26th - 29 th, 1960. [Report of the general secretariat November 1, 1957 - October 25, 1960] (N.pl.)
Gestencild.